The mystery of the vanishing sources: how New Testament scholars superficially and uncritically identified the ancient background of Luke 8:43-48, Acts 5:15, and Acts 19:12 - Paschke, Boris (Biblische Notizen, 2006)
The present article demonstrates that many New Testament scholars identified the historical background of the indirect healings reported in Luke-Acts (Lk 8:43-48; Acts 5:15; 19:12) in a very superficial and uncritical manner. It became obvious, for example, that statements concerning ancient practices and beliefs are not or insufficiently backed up by ancient texts. Instead of carefully studying the available Greco- Roman and Jewish primary sources, many scholars took over (wrong) conclusions from secondary literature too quickly and uncritically. Consequently, these scholars ended up with an inadequate picture of the ancient background. This, again, can easily result in an improper exegesis of the New Testament texts in question. The deterrent examples presented in the present article should serve as an indication of the need for more careful and critical identification of the historical background of New Testament texts.